Pre-service teachers’ experiences in selecting and proposing challenging tasks in secondary classrooms - Santos, Leonor (2020)
This study aims to know if pre-service secondary school mathematics teachers are able to select, adapt or design appropriate challenging tasks and what are the main challenges that they face when working with challenging tasks in the classroom. The study is qualitative, based on observation and interviews. The participants are two preservice teachers at the 2nd (and final) year of their master of teaching degree. The results show that the preservice teachers, albeit facing several constrains, were able to find and adapt interesting tasks. They also identified several challenges in this activity, in the planning phase, during students’ autonomous work and, most especially, during the whole class discussions.